Comparison of Dental Students' PAT Scores with Their Performance in Preclinical Technique Courses: Identifying the Need for Early Interventions. Issue 4 (1st April 2018) - Schultz-Robins, Michele; Markowitz, Kenneth; DeCastro, Jeanette; Jiang, Shuying
Abstract : The aim of this study was to determine if lower scores on the Perceptual Ability Test (PAT) of the Dental Admission Test (DAT) predicted which dental students required remediation in three preclinical restorative dentistry courses at Rutgers School of Dental Medicine. The academic records of 489 dental students from the graduating Classes of 2010 through 2015 were evaluated. The results showed that, for all three courses (Preclinical General Dentistry I, Preclinical General Dentistry II, and Preclinical Fixed Prosthodontics), the remediating students had significantly lower mean PAT scores than did the passing students. A one‐unit decrease in a student's PAT score was associated with a 43% increase in the odds of remediating the Preclinical General Dentistry I lab, a 29% increase in the odds of remediating the Preclinical Fixed Prosthodontics lab, and a 47% increase in the odds of remediating the Preclinical General Dentistry II lab. The mean PAT score for passing students was 18.84 (standard deviation 2.35), and the mean PAT score for students requiring remediation was 17.03 (standard deviation 2.18). Studies like this can be useful because if students at risk of failing these courses are identified early and appropriate supports are provided, the need for remediation may be reduced if not eliminated.